Synthesis, antibacterial, antifungal, antioxidant, cytotoxicity and molecular docking studies of thiazole derivatives - Keshav B. Gangurde; Rahul A. More; Vishnu A. Adole; Dattatray S. Ghotekar (Results in Chemistry, 2024)
The emergence of numerous pandemics and microbial resistance has necessitated the development of novel heterocyclic compounds with potent biological effects. Five new (E)-2-((5-(1H-benzo[d]imidazol-1-yl)-3-methyl-1-phenyl-1H-pyrazol-4-yl)methylene)hydrazineyl)-4-(aryl)thiazole derivatives (9a-e) were synthesized through a one pot multicomponent reaction involving 5-(1H-benzo[d]imidazol-1-yl)-3-methyl-1-phenyl-1H-pyrazole-4-carbaldehyde, thiosemicabazide and various substituted phenacyl bromides. FT-IR, 1H NMR, and 13C NMR spectroscopic techniques were used to characterize the newly synthesized benzimidazole-pyrazole clubbed thiazole hybrids. The synthesized compounds were screened for antibacterial activity against E. coli, B. subtilis, B. megaterium, and S. aureus and antifungal activity against A. niger, A. oryzae, Rhizophus spp., and C. albicans. All newly synthesized compounds exhibited potent antibacterial action against all tested strains. Besides, % radical scavenging activity was also evaluated and results showed good antioxidant potential of the synthesized compounds. The cytotoxicity study revealed that synthesized compounds has no to less toxicity as compared to standard Triton X 100. Molecular docking simulations against DNA gyrase (PDB: 4URO) revealed binding interactions and MESP plots confirmed the binding locations.